Psychosocial Effects of the COVID-19 Pandemic on Patients With Schizophrenia and Their Caregivers - Caqueo-Urízar, Alejandra; Urzúa, Alfonso; Ponce-Correa, Felipe; Ferrer, Rodrigo (Frontiers in Psychology, 2021)
The aim of this study was to analyze the psychosocial effects of the COVID-19 pandemic on 120 patients with schizophrenia, and their caregivers (control group), in the city of Arica, northern Chile. The results showed that patients with schizophrenia who had been in quarantine for almost a year showed similar levels of concern as their caregivers in the domains of health and social life. However, caregivers showed significant differences from patients in the areas of income, concern, and employment status. In addition, patients who were infected with COVID-19 showed lower levels of well-being and worse psychological recovery.